Interaction of silver atomic quantum clusters with living organisms: bactericidal effect of Ag3 clusters mediated by disruption of topoisomerase–DNA complexes. Issue 12 (7th September 2015) - Neissa, J.; Pérez-Arnaiz, C.; Porto, V.; Busto, N.; Borrajo, E.; Leal, J. M.; López-Quintela, M. A.; García, B.; Dominguez, F.
Abstract : Ag3 clusters distort DNA conformation altering the binding of doxorubicin and enzymes. As a novel aspect, the Ag3 bactericidal activity is described. Abstract : Essential processes for living cells such as transcription and replication depend on the formation of specific protein–DNA recognition complexes. Proper formation of such complexes requires suitable fitting between the protein surface and the DNA surface. By adopting doxorubicin (DOX) as a model probe, we report here that Ag3 atomic quantum clusters (Ag-AQCs) inhibit the intercalation of DOX into DNA and have considerable influence on the interaction of DNA-binding proteins such as topoisomerase IV, Escherichia coli DNA gyrase and the restriction enzyme HindIII. Ag-AQCs at nanomolar concentrations inhibit enzyme activity. The inhibitory effect of Ag-AQCs is dose-dependent and occurs by intercalation into DNA. All these effects, not observed in the presence of Ag + ions, can explain the powerful bactericidal activity of Ag-AQCs, extending the knowledge of silver bactericidal properties. Lastly, we highlight the interest of the interaction of Ag clusters with living organisms, an area that should be further explored due to the potential consequences that it might have, both beneficial and harmful.